Fiscal stimulus with learning-by-doing - Antonello d' Alessandro; Giulio Fella (Queen Mary University of London, School of Economics and Finance, 2017)
Using a structural VAR analysis, we document that an increase in government purchases raises private consumption, total factor productivity (TFP) and the real wage. This poses a puzzle for both neoclassical and New-Keynesian models. We extend a standard New-Keynesian model to allow for skill accumulation through past work experience, following Chang, Gomes and Schorfheide (2002). An increase in government spending increases hours and induces skill accumulation and higher measured TFP and real wages in subsequent periods. Future marginal costs fall lowering the expected rate of ination and, through the monetary policy rule, the real interest rate. Consumption increases as a result.
Keywords: E62; E63; 330; Fiscal policy transmission; consumption; real wage